2010
DOI: 10.1016/j.amepre.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Heat Illness Among Latino Farm Workers in North Carolina

Abstract: Background Symptoms of occupational heat illness provide an early warning that workers are in potentially life-threatening environmental conditions. Purpose This analysis was designed to assess the extent to which strategies to reduce the health impact of extreme heat were associated with the prevalence of heat illness among Latino farmworkers. Methods Between June and September 2009, 300 Latino men and women participated in a cross-sectional survey about farmworker health. Participants reported whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 8 publications
3
78
1
1
Order By: Relevance
“…An earlier study on heat-related mortality in North Carolina found that almost half of all occupational heat-related deaths from 1977 to 2001 were among farm workers [35]. Several risk factors have been identified among this demographic, including the exertional nature of their work (many laborintensive crops are typically harvested in July), excessive clothing, poor housing conditions, lack of preventative training, lack of access to health care, and underlying illness or disease [19,34,[36][37][38]. Since we did not have access to any individual information on the circumstances surrounding each ED visit, we could not confirm what specific occupations were in fact associated with HRI.…”
Section: Discussionmentioning
confidence: 97%
“…An earlier study on heat-related mortality in North Carolina found that almost half of all occupational heat-related deaths from 1977 to 2001 were among farm workers [35]. Several risk factors have been identified among this demographic, including the exertional nature of their work (many laborintensive crops are typically harvested in July), excessive clothing, poor housing conditions, lack of preventative training, lack of access to health care, and underlying illness or disease [19,34,[36][37][38]. Since we did not have access to any individual information on the circumstances surrounding each ED visit, we could not confirm what specific occupations were in fact associated with HRI.…”
Section: Discussionmentioning
confidence: 97%
“…Hydration is a key issue among farm workers since it is also reasonable that during several consecutive days of working in hot temperatures, workers may begin a shift without fully rehydrating from the previous day 18,26) . A recent study of farm workers in North Carolina reported that while 94% of respondents worked in conditions of extreme heat, 40% of them reported symptoms of heat illness 27) . Furthermore, workers with authorization drank more water, took more breaks and changed work hours and activity to a greater extent than those working without authorization.…”
Section: Discussionmentioning
confidence: 99%
“…always very flexible and a series of hot, warm days with reduced rainfalls increase the requirements for artificial irrigation, forcing AWs to perform their activities even during HWs [30,33,34,[45][46][47]. Not coincidentally, in our survey the daily average rate of OIs was similar from June to August, being higher in the calendar months of September and June, with the significant lack of effect for the central months of July and August, otherwise characterized by higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Available estimates suggest that the increased magnitude and frequency of extreme events would ultimately lead to a significant excess in morbidity and mortality for cardiovascular and respiratory illnesses, and that the climate changes will presumptively increase both the incidence and the severity of these effects [4][5][6][7][8][9][10][11][12], in particular in Mediterranean-like climates [13]. migrant background [33,34], part-time or seasonal workers, and "hobby farmers" (i.e., subjects running a farm as a hobby rather than as means of making a living), the number of which usually surges during hot moths and the harvest season, including subjects who otherwise spend little time outdoor [25,29,35]. Hence, many AWs may continue to work beyond a safe heat exposure limit as they are unaware of the risks associated with the heat exposure or have inappropriate knowledge of the preventive measures, as avoiding the hottest hours of the day for most strenuous physical exertion or increasing the water intake, in particular during the HWs [13,30].…”
Section: Introductionmentioning
confidence: 99%